TEACHER PROBLEMATICS IN MATHEMATICS LESSONS AT SDN 3 BANDA ACEH CITY - Yusari, Rita; Sari, Siti Mayang (Sensei International Journal of Education and Linguistic, 2024)
This research aims to see what problems teachers are facing in teaching Mathematics at SDN 3 Banda Aceh City and what solutions are provided by teachers to students while the teaching and learning process is taking place in the classroom. The research method used is a qualitative approach, with the type of research data collection using observation, interviews and documentation methods with research subjects namely grade 1 elementary school teachers. The results of the research show that there are several problems experienced by many teachers in teaching mathematics, including:1. What are the factors that make it difficult for us as teachers to teach Mathematics? 2. What curriculum is currently used in schools? 3. How interested are students in taking mathematics lessons? 4. Do students easily memorize formulas? 5. How do teachers develop talent for teaching mathematics ?. The solutions offered regarding the difficulties faced are: 1) Teachers must provide students with learning motivation for basic Mathematics concepts; 2) Teachers must understand the meaning of independent curriculum and can explore it with students without coercion; 3) Teachers must be more creative in using appropriate learning media, methods and strategies to make it easier for students to memorize mathematical formulas; 5) Teachers must participate actively in teacher working groups (KKG).